2006
DOI: 10.1111/j.1365-2826.2006.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine‐ and Amphetamine‐Regulated Transcript is Overexpressed in the Anteroventral Periventricular Nucleus of Pregnant Rats

Abstract: The anteroventral periventricular nucleus (AVPV) is sexually dimorphic, presenting a higher neuronal density in females. The AVPV contains a dense collection of oestrogen and progesterone receptors and has been related to the modulation of gonadotrophin-releasing hormone (GnRH) secretion and gene expression in response to circulating hormonal levels. It has been suggested that cocaine- and amphetamine-regulated transcript (CART) is also related to reproductive control because CART immunoreactive fibres are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…However, E did not regulate basal CART expression in that area (Nedungadi & Briski 2007). During pregnancy, when serum P is elevated, rats show increased CART expression in the anteroventral periventricular nucleus (AVPV), a nucleus governing maternal behavior and GnRH release (Valera et al 2006). The latter data are consistent with our observation that P increased CART immunostained area, as well as the number of detectable neurons in the midbrain.…”
Section: Effects Of E and P Administrationsupporting
confidence: 89%
See 1 more Smart Citation
“…However, E did not regulate basal CART expression in that area (Nedungadi & Briski 2007). During pregnancy, when serum P is elevated, rats show increased CART expression in the anteroventral periventricular nucleus (AVPV), a nucleus governing maternal behavior and GnRH release (Valera et al 2006). The latter data are consistent with our observation that P increased CART immunostained area, as well as the number of detectable neurons in the midbrain.…”
Section: Effects Of E and P Administrationsupporting
confidence: 89%
“…CART mRNA and protein are expressed in various areas of the brain of humans, monkeys and rats, including hypothalamus, pituitary and adrenal (Douglass et al 1995;Vrang 2006;Koylu et al 1997;Valera et al 2006); limbic system (Hurd & Fagergren 2000), and sensory cortex (Hurd & Fagergren 2000). CART is modified by posttranslational processing and several CART peptide fragments exist in the brain (Dylag et al, 2006;Thim et al 1999;Kuhar & Yoho 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a very small population of CART-immunoreactive fibers that do contain SOM, CCK or SP in this area. CART and NPY are both major regulatory peptides involved in feeding behavior and other neurobiologic effects [16,21,36]. They are both found in areas associated with feeding in mammals, but they act inversely to each other [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CART is considered to be an anorexigenic peptide. Although most studies have looked at CART action in the brain areas related to feeding behavior, a recent investigation has suggested that CART may play a role in the regulation of gonadotropin release [20], as well as in the mechanism involved in the initiation of maternal behavior [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recently discovered neuropeptide, co-caine-and amphetamine-regulated transcript (CART), has also been reported to be involved in the neural regulation of reproduction. CART is expressed in the hypothalamus, the key area involved in the central regulation of reproductive processes (Valera et al, 2006;Vrang et al, 2006), and CART-containing axon terminals were observed on GnRH-containing neurons in the hypothalamus of the Siberian hamster and the rat (Leslie et al, 2001;Rondini et al, 2004). CART mRNA and peptide are abundantly present in the pituitary (Koylu et al, 1997;Thim et al, 1999), and localized in the cells that secrete follicle stimulating hormone and luteinizing hormone (LH) (Kuriyama et al, 2004).…”
mentioning
confidence: 99%